The impact of credit risk on the profitability of development financial institutions / Sabarinani Sabar - Sabar, Sabarinani (2017)
This study is conducted to investigate the credit risk and to evaluate its effect on the profitability of Development Financial Institutions in Malaysia. The data were recovered from income statement, balance sheet and notes of 5 Malaysian DFIs in 2008 to 2016. This study uses multiple regressions test to measure the effect of credit risk towards the profitability of the DFIs in Malaysia. The period of time of this study is 2008-2016; it is due to the issue related to credit risk that happen between the mentioned years. On the other hand, to measure the DFIs performance, this study only uses profitability of the banks. Moreover, Credit problem that comes from the economic factor is not covered in this study. This is not the first study of the credit risk in Malaysia. However, this is the first study that conducted which is more specific on the financial industry in Malaysia which only focused on the Development Financial Institution. The finding of this study shows credit risk indicators non-performing loan and capital adequacy ratio displays a positive relationship with DFIs financial performance.